(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
This study compiles the scientific literature of the last 10 years on microplastics and their impact on macroinvertebrates in freshwater ecosystems in Colombia. Despite their environmental and public health relevance, research on these emerging contaminants is scarce compared to studies in marine systems in the country.